Stone mortars in Roman Cisalpine: new specimens (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The mortar, made of stone or marble, represents artifact in Cisalpine widespread elsewhere in the Roman world. the morphologies are substantially grouped into two basic shapes: type 1 presents a hemispherical bowl more or less flattened, Type 2 is characterized by a conical reverse body, more or less flared. In the mortars were subjected to pounding and grinding, using a pestle driven by hand, raw materials of various origin. The fields of application were mainly three: alimentary, officinal and cosmetic. In some cases the generic definition of mortar is applied improperly to marble containers probably only be used for ornamental. It 'also demonstrated the use of artifacts attributable to type 2 as a function of urns. Therefore, in reference to decontextualized pieces, you should use a definition not unique, reflecting the different possible meanings of the artifact.
Keywords: mortar; stone; marble; hemispherical; conical; alimentary; officinal; cosmetic; ornamental; urns